Mastering project management : key skills in ensuring profitable and successful projects - Lake, Cathy (Masters in management series., 1997)
This volume enables managers to review, extend and sharpen their project management skills, promoting individual development, personal and organizational effectiveness. Practical features include key questions, action checklists, activities and guides to best practice.